2015
DOI: 10.1242/jeb.123612
|View full text |Cite
|
Sign up to set email alerts
|

The neonicotinoid clothianidin interferes with navigation of the solitary bee Osmia cornuta in a laboratory test

Abstract: Pollinating insects provide a vital ecosystem service to crops and wild plants. Exposure to low doses of neonicotinoid insecticides has sub-lethal effects on social pollinators such as bumblebees and honeybees, disturbing their navigation and interfering with their development. Solitary Hymenoptera are also very important ecosystem service providers, but the sub-lethal effects of neonicotinoids have not yet been studied well in those animals. We analyzed the ability of walking Osmia to remember a feeding place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
2
39
0
1
Order By: Relevance
“…Comparative studies have found adult O. bicornis to be more sensitive to clothianidin-spiked nectar than either honeybees (Heard et al, 2017) or honeybees and bumblebees (Sgolastra et al, 2016) though effects became apparent over different time-scales. A study of the closely related O. cornuta revealed that acute exposure to clothianidin can impair navigational behaviour under laboratory conditions (Jin et al, 2015). Sandrock et al (2014) provided caged adult bees with sucrose solution spiked with thiamethoxam and clothainidin and found that females produced fewer nests, with fewer brood cells than those completed by female bees provided with uncontaminated sucrose solution.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have found adult O. bicornis to be more sensitive to clothianidin-spiked nectar than either honeybees (Heard et al, 2017) or honeybees and bumblebees (Sgolastra et al, 2016) though effects became apparent over different time-scales. A study of the closely related O. cornuta revealed that acute exposure to clothianidin can impair navigational behaviour under laboratory conditions (Jin et al, 2015). Sandrock et al (2014) provided caged adult bees with sucrose solution spiked with thiamethoxam and clothainidin and found that females produced fewer nests, with fewer brood cells than those completed by female bees provided with uncontaminated sucrose solution.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous global factors are thought to contribute to this alarming phenomenon, including habitat loss and fragmentation, suboptimal diet, diseases and the detrimental effects of sublethal, chronic pesticide exposure (Goulson, Nicholls, BotĂ­as, & Rotheray, ; Vanbergen et al, ). Besides affecting pollinator navigation abilities (Fischer et al., ; Henry et al., ; Jin, Klein, Leimig, Bischoff, & Menzel, ; Stanley, Russell, Morrison, Rogers, & Raine, ), cognitive abilities (Decourtye, Devillers, Cluzeau, Charreton, & Pham‐Delègue, ; Farooqui, ; Gauthier, ; Kessler et al., ; Piiroinen & Goulson, ; Stanley, Smith, & Raine, ; Williamson, Baker, & Wright, ; Williamson, Moffat, et al., ) and reproduction (Baron, Raine, & Brown, ; Sandrock et al., ; Whitehorn, O'Connor, Wackers, & Goulson, ), the immune suppressive effect of sublethal pesticide doses and the resulting elevated susceptibility of pollinators to pathogens (Baron et al., ; Brandt, Gorenflo, Siede, Meixner, & BĂźchler, ; Di Prisco et al., ; Doublet, Labarussias, de Miranda, Moritz, & Paxton, ; Fauser‐Misslin, Sadd, Neumann, & Sandrock, ; HernĂĄndez LĂłpez et al., ; previous studies summarized in James & Xu, ) are of particular concern (SĂĄnchez‐Bayo et al., ).…”
Section: Of Pollinators Pesticides and Parasitesmentioning
confidence: 99%
“…Assessing the impact of pesticides on pollinator health by sublethal chronic exposure requires a holistic view of the problem. In recent years, research has started to uncover the side‐effects of sublethal neonicotinoid exposure on cognitive abilities, including pollinator navigation and learning (Decourtye et al., ; Farooqui, ; Fischer et al., ; Gauthier, ; Goulson et al., ; Henry et al., ; Jin et al., ; Kessler et al., ; Piiroinen & Goulson, ; Stanley et al., , ; Williamson, Baker, et al., ; Williamson, Moffat, et al., ). A similar intensity of research effort now needs to be focused on the sublethal effects of neurotoxic pesticides on insect immunity.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species are specialized for certain flowers where honeybee pollination is less effective and, thus, they contribute significantly to pollination. Although some studies exist on the effects of neonicotinoids on bumblebees (e.g., Gill et al ), studies on solitary bees are sparse (e.g., Jin et al ). Because their worldwide decline is apparent, the maintenance of the biological diversity in many ecosystems is severely threatened, and immediate measures are needed to protect wild bee populations.…”
Section: In Response: a Perspective From Academiamentioning
confidence: 99%